Study of the biblio-integrative characteristics of the Spanish journal of public health: An analysis of the promotion and prevention - Vallejos Saldarriaga, José (2015)
The objective of this work is to perform a bibliointegrative analysis of the Spanish Journal of Public Health and establish the preference they give to the prevention and promotion, considering for this purpose, the articles original papers, original brief and special collaboration published in the period 2003 - 2010. 365 articles were analyzed. Between 2003 and 2010 original 232 articles (63.6 %), 15 Original short articles (4.1 %) and 118 special collaboration (32.3 %) of a total of 365 articles, 336 (92.05 %) were published in spanish publications and 29 (7.95 %) to foreign publications. The thematic highlights regarding surveillance, planning and health management, infectious and chronic diseases. The type of publication with the highest number of empirical articles is 245 (67.12 %) and the theoretical 120 (32.88 %). The areas of public health with more contributions are: health management, surveillance, prevention and health promotion. Overall, the Spanish Journal of Public Health publishes promotion and prevention of disease in 41.15 % (150), distributed in different areas.